Retrospective comparison of chemoradiotherapy followed by adjuvant chemotherapy, with or without prior gliadel implantation (carmustine) after initial surgery in patients with newly diagnosed high-grade gliomas - Noël, Georges; Schott, Roland; Froelich, Sébastien; Gaub, Marie-Pierre; Boyer, Patrick; Fischer-Lokou, David; Dufour, Patrick; Kehrli, Pierre; Maitrot, Daniel (International journal of radiation oncology, biology, physics, 2012)
Retrospective study of patients treated for high-grade glioma, with or without biodegradable carmustine wafers and according to the Stupp protocol. Between May 2007 and June 2008, 65 patients underwent surgery for high-grade glioma, 28 had implantation of Gliadel and 37 patients did not. Patients received radiotherapy with concomitant temozolomide followed by 5 consecutive days of temozolomide every month for 6 months. Overall median follow-up was 17.1 months; the median relapse-free survival (RFS) was 14 months with a RFS of 54% at 12 months, and 38% at 24 months. For patient with and without Gliadel, median and 1-year RFS were 12.9 months and 52% vs. 14 months and 42%, respectively (p = 0.89). According to pathology, Gliadel did not influence RFS of patients with Grade III or glioblastoma. However, for all patients, in multivariate analysis, non-methylated methylguanine methyltransferase (MGMT) was the only unfavorable prognostic factor of RFS (p = 0.017; HR 2.8; CI [1.2-7]). Median overall survival (OS) was 20.8 months; the OS rate at 12 months was 78.5%, and at 24 months 35.4%. For patients treated with and without Gliadel, median and 1-year OS were 20.6 months and 78.6% vs. 20.8 months and 78.4%, respectively. According to pathology, Gliadel did not influence OS of patients with Grade III or glioblastoma. For all patients, in multivariate analysis, unfavorable prognosticators for OS were non-methylated MGMT (p = 0.001; HR: 6.5; CI [2-20]) and irradiation dose <60 Gy (p = 0.02; HR: 6.3; CI [2-20]). With carmustine wafers, before irradiation, median gross tumor volume plus edema was 84 mL (27-229), whereas it was 68 mL (10-362) without carmustine (p = nonsignificant). Four cases of Grade 3 thrombopenia occurred, all in the carmustine wafer group. In patients with high-grade gliomas, adding Gliadel before performing a Stupp protocol did not improve survival.